2019
DOI: 10.1371/journal.pone.0219251
|View full text |Cite
|
Sign up to set email alerts
|

Beyond asking: Exploring the use of automatic price evaluations to implicitly estimate consumers’ willingness-to-pay

Abstract: Explicit consumers responses are often adverse for the validity of procedures used to estimate consumers’ willingness-to-pay (WTP). This paper investigates if price evaluations occur automatically and to what extent these automatic processes can be used to implicitly estimate consumers’ WTP. An adapted version of the task-rule congruency (TRC) paradigm was used in two studies. Results of the first study provided evidence for the notion that prices are automatically evaluated. However, the used procedure had li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…Recent pricing studies have shown that exposure to price information elicits physiological, psychological and emotional reactions (Adaval, 2013;Coulter, 2013). Price evaluations are likely to be construed via automatic interpretations of these non-deliberate reactions (Cheng & Monroe, 2013a;Dezwaef, Cracco, Demanet, Desmet, & Brass, 2019) and Peine, Heitmann, & Herrmann (2009) demonstrated that effortful cognitive processing of price information automatically triggers implicit emotional responses towards prices which affect purchase decisions. Hence, price evaluations seem to be the result of both nondeliberate, cognitive and affective processing.…”
Section: Introductionmentioning
confidence: 99%
“…Recent pricing studies have shown that exposure to price information elicits physiological, psychological and emotional reactions (Adaval, 2013;Coulter, 2013). Price evaluations are likely to be construed via automatic interpretations of these non-deliberate reactions (Cheng & Monroe, 2013a;Dezwaef, Cracco, Demanet, Desmet, & Brass, 2019) and Peine, Heitmann, & Herrmann (2009) demonstrated that effortful cognitive processing of price information automatically triggers implicit emotional responses towards prices which affect purchase decisions. Hence, price evaluations seem to be the result of both nondeliberate, cognitive and affective processing.…”
Section: Introductionmentioning
confidence: 99%
“…First, we expected that ambiguous prices would result in slower price evaluations compared to unambiguous prices. This effect was observed in our earlier work and is assumed to provide information about consumers' IRPs (Dezwaef, Cracco, Demanet, Desmet, & Brass, 2019;Dezwaef et al, 2020). That is, if prices are neither clearly 'cheap' nor 'expensive', more conflict between two response options should be experienced and responses should be slower.…”
Section: Introductionmentioning
confidence: 73%
“…Foremost, we expected the drift rate (v) to be influenced by the ambiguity of the price. Based on the results of previous work (Dezwaef et al, 2019(Dezwaef et al, , 2020 we expected that more ambiguous prices would result in lower drift rates, as more evidence would need to be accumulated to decide between 'cheap' or 'expensive'. However, it is also possible that differences in RTs are not related to the ambiguity of the price but instead to the retrieval of the IRP.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the initial bid is derived from a market analysis from similar products, id est different brands of fresh lactose-free milk. The market price was used as a starting point, since consumers use reference prices as a threshold to evaluate the selling price of products, which on its turn, impacts subsequent purchase decisions [53]. Successively, the design and the ranges of the bid value sets were determined and tested from the focus group discussion and the pre-test survey.…”
Section: Methodsmentioning
confidence: 99%